Soil deterioration assessment as an indicator of land degradation in dry land ecosystems based on a multi-criteria approach, North Halmahera, Indonesia - Sofyan, Adnan; Hartati, Tri Mulya; Ishak, Lily; Aji, Krishna; Hartono, Gunawan; Tangge, Nurul Ainun; Achmad, Fitriani H. (Journal of Degraded and Mining Lands Management, 2026)
Land degradation is one of the biggest challenges to agricultural sustainability in tropical regions, mainly due to the pressures of land intensification, climate change, and unsustainable soil management practices. Soil deterioration can occur in physical, chemical, and biological aspects, thereby reducing the soil's capacity to support agricultural productivity. This study aimed to evaluate the status of soil deterioration through a multi-parameter approach in the dryland ecosystem of North Halmahera, Indonesia. The parameters analyzed include solum thickness, surface stoniness, fraction composition, bulk density, porosity, water permeability, pH, electrical conductivity (EC), redox potential, and microbial population. The results showed that all points experienced degradation, with four points (T1, T2, T4, T5) classified as moderately deteriorated and the other four points (T3, T6, T7, T8) classified as severely deteriorated. The main factor of deterioration was very high salinity (29-50 mS/cm), far exceeding the critical threshold, which caused osmotic stress and ion toxicity to plants, low redox (100 mV), high bulk density (1.83-1.99 g/cm³), extreme porosity (>70%), and low microbial population (<10² CFU/g) at several points. However, the soil pH is relatively neutral (6.8-7.0), so it is not a limiting factor. The results of this study are used as reference material for sustainable land management to achieve the sustainable development goals.